Towards a framework for transferring technology knowledge between facilities - McBeath, Andre; Ball, Peter D. (Emerald, 2012)
Purpose - The transfer of technical know-how is now recognised as an essential component in the globalised expansion of multinational companies. As these companies offshore or outsource their operations the success of the new facility can depend on the ability to convey both tacit and explicit knowledge willingly during all phases of the transfer. There is a lack of clarity in current literature on the success factors for effective transfer of knowledge on production parts transfer and an absence of frameworks. The purpose of the research reported in this paper is to examine documented success factors and propose an integrated framework. Design/methodology/approach - Peer reviewed literature was used to establish dominant themes on knowledge-sharing from which interview and survey were designed and undertaken to establish motivating factors. Findings - Five key themes required for successful knowledge transfer were established for moving parts to new production facilities: willingness to share information, willingness to receive information, explicit knowledge transfer, tacit knowledge transfer and verification. These were then assembled into a transfer of technical intellect framework for knowledge transfer to new facilities. Research limitations/implications - The research draws from the experience of practitioners across multiple parts transfers rather than examining a specific transfer. This work brings research not previously brought together. It draws from the literature and a significant survey of a large multi-site engineering company and future work needs to be carried out to examine the generalisability of the work. Practical implications - The proposed framework guides the tacit as well as explicit transfer of technical knowledge of production parts between facilities. Originality/value - The research identifies the key themes and motivating factors for transferring tacit product knowledge to another organisation.
Keywords: Tacit knowledge transfer, Parts outsourcing, Facility transfer, Technical know-how, Knowledge management, Information transfer, Outsourcing